2021
DOI: 10.1177/10600280211021925
|View full text |Cite
|
Sign up to set email alerts
|

Sedation Usage in COVID-19 Acute Respiratory Distress Syndrome: A Multicenter Study

Abstract: Background Patients with COVID-19 acute respiratory distress syndrome (ARDS) have been shown to have high sedation requirements. Objective The purpose of this study was to compare sedative use between patients with COVID-19 ARDS and non-COVID-19 ARDS. Methods This was a retrospective study of patients with COVID-19 ARDS compared with historical controls of non-COVID-19 ARDS who were admitted to 2 hospitals from March 1, 2020, to April 30, 2020, and April 1, 2018, to December 31, 2019, respectively. The primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 16 publications
3
21
0
Order By: Relevance
“…These findings were consistent with three previous studies [6,11,12], which reported an increased need of sedative drugs in COVID-19 ARDS patients when compared to non-COVID patients; however, study groups were not comparable (i.e., different characteristics and severity; unmatched cohorts) and the control non-COVID group could not reflect the actual management of ARDS patients on MV [11]. Our findings might have some important implications for clinical practice: (a) sedation protocols, which are often based on one single drug, should be revised in COVID-19 patients with ARDS on MV (i.e., more combination therapy) to obtain the same level of sedation than in non-COVID ARDS patients; (b) if NMBAs are more frequently administered, the risk for long-term complications (i.e., ICUacquired weakness) should be carefully evaluated; (c) the high afflux of patients and the requirement for increased doses and prolonged duration of sedatives and NMBAs might result in limited drug availability and might result in significant organizational issues for drug supply and stockage during the pandemic.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…These findings were consistent with three previous studies [6,11,12], which reported an increased need of sedative drugs in COVID-19 ARDS patients when compared to non-COVID patients; however, study groups were not comparable (i.e., different characteristics and severity; unmatched cohorts) and the control non-COVID group could not reflect the actual management of ARDS patients on MV [11]. Our findings might have some important implications for clinical practice: (a) sedation protocols, which are often based on one single drug, should be revised in COVID-19 patients with ARDS on MV (i.e., more combination therapy) to obtain the same level of sedation than in non-COVID ARDS patients; (b) if NMBAs are more frequently administered, the risk for long-term complications (i.e., ICUacquired weakness) should be carefully evaluated; (c) the high afflux of patients and the requirement for increased doses and prolonged duration of sedatives and NMBAs might result in limited drug availability and might result in significant organizational issues for drug supply and stockage during the pandemic.…”
Section: Discussionsupporting
confidence: 94%
“…Whether COVID-19 ARDS patients receive different sedation strategies to non-COVID ARDS patients remains poorly described. In one study [6], 92 patients with COVID-19 related ARDS required higher total median doses of propofol and were more likely receive intravenous lorazepam than 37 non-COVID ARDS patients; however, the two study groups were significantly unbalanced for several important variables and it remains difficult to conclude whether these differences in sedation requirement were due to COVID-19 or patients' characteristics. Similarly, neuromuscular blocking agents (NMBA) have been largely used in COVID-19 patients with severe respiratory impairment on mechanical ventilation [7]; however, limited data exist to assess whether NMBA requirements would be higher in COVID-19 and other patients.…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence rate of 72.4% of early deep sedation is also higher than that seen in recent pre-COVID publications and further highlights the rapidly adopted changes in sedation practice that occurred with the COVID pandemic [ 17 , 19 ]. These findings are consistent with prior reports that documented high sedative and neuromuscular blockade use in COVID patients[ 20 , 21 , 36 39 ]. Further, our findings highlight the static nature in the approach to sedation in the early deep sedation group: (1) > 50% experienced deep sedation throughout the first week of mechanical ventilation; and (2) 33% were deeply sedated until death.…”
Section: Discussionsupporting
confidence: 93%
“…The recommendations for analgesia/sedation in mechanically ventilated pregnant patients are generally similar to nonpregnant individuals [7]. Many intubated patients with severe COVID-19 infection require high doses of analgesia/sedation with or without a neuromuscular blocking agent (NMBA) [8]. This usually increases the risk of delirium and impacts weaning from ventilation, length of stay, mortality, and costs [9][10][11].…”
Section: Introductionmentioning
confidence: 99%